Carbon nanodots from used green tea biochar: antibacterial applications and antibiofilm carbon coatings - E. Elsa Sharon; Jae-Wook Oh; Judy Gopal (Journal of Applied Science and Engineering)
Green tea has been famous and well-known for various reasons, its value has been recognized from time immemorial for its bioactivity. Green tea leaves also come as handy green tea bags, usually green tea is extracted once in hot water and then the leaves are discarded. The present study reports the successful reuse of these used green tea leaves from tea bags for the synthesis of carbon nanodots. Used green tea leaves biochar was obtained by heat treatment in a muffle furnace and carbon nanodots were extracted from the biochar. The carbon nanodots were characterized to confirm their morphological and chemical characteristics. The antibacterial activity was tested against pathogenic coliforms as well as oral bacteria. The results indicated that the indigenously prepared carbon nanodots exhibited significant antibacterial activity. Carbon coatings were prepared from these used green tea biochar derived carbon nanodots using a simple dip coating method and their antibiofilm activity was demonstrated. For the first time, we report the successful synthesis of antibacterial carbon nanodots from used green tea biochar.